2020
DOI: 10.1002/1873-3468.13909
|View full text |Cite
|
Sign up to set email alerts
|

Substrate specificities of inteins investigated by QuickDrop‐cassette mutagenesis

Abstract: Inteins catalyze self-excision from host precursor proteins while concomitantly ligating the flanking substrates (exteins) with a peptide bond. Noncatalytic extein residues near the splice junctions, such as the residues at the À1 and +2 positions, often strongly influence the protein-splicing efficiency. The substrate specificities of inteins have not been studied for many inteins. We developed a convenient mutagenesis platform termed "QuickDrop"-cassette mutagenesis for investigating the influences of 20 ami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 53 publications
0
13
0
Order By: Relevance
“…10 The structure of Cat is similar to that of DnaE inteins, such as Npu (PDB ID: 2KEQ, RMSD 1.45 Å over 92 aligned Cα atoms) and Ssp (PDB ID: 1ZDE, RMSD 1.34 Å over 90 aligned Cα atoms) with the notable exception that Npu and Ssp have an additional helix, which is absent in Cat. 12,25,26 In the Cat active site, a serine residue (Ser 75 ) replaces the threonine located in the canonical TXXH B-block motif (Figure S3c). 27,28 The carbonyl oxygen of C1A is proximal to the amide proton (2.4 Å) and the hydroxyl proton (3.7 Å) of Ser 75 (Figure 4c).…”
Section: Solution Structure Of An Atypical Split Intein Complexmentioning
confidence: 99%
See 1 more Smart Citation
“…10 The structure of Cat is similar to that of DnaE inteins, such as Npu (PDB ID: 2KEQ, RMSD 1.45 Å over 92 aligned Cα atoms) and Ssp (PDB ID: 1ZDE, RMSD 1.34 Å over 90 aligned Cα atoms) with the notable exception that Npu and Ssp have an additional helix, which is absent in Cat. 12,25,26 In the Cat active site, a serine residue (Ser 75 ) replaces the threonine located in the canonical TXXH B-block motif (Figure S3c). 27,28 The carbonyl oxygen of C1A is proximal to the amide proton (2.4 Å) and the hydroxyl proton (3.7 Å) of Ser 75 (Figure 4c).…”
Section: Solution Structure Of An Atypical Split Intein Complexmentioning
confidence: 99%
“…strain PCC6803 (Ssp) and Nostoc Punctiforme (Npu), fragment assembly was shown to exploit a disorder to order structural transition to produce the topologically intertwined Hedgehog/Intein (HINT) domain. 7,8,12 Alternatively, a split intein from the DNA polymerase of Nanoarchaeum equitans (Neq) employs an extensive structural rearrangement of a pre-folded Neq N-intein upon C-intein interaction. 13 Each of these two mechanisms provides precise control of assembly through coordinated structural rearrangements.…”
Section: Introductionmentioning
confidence: 99%
“…Design of extein in the present study offers a competitive choice under the strategy to maintain the number of Cys in hinge. Local sequences at around junction between intein and extein is the determinant of the reaction efficiency as known for protein splicing 32 36 , 43 , but both N- and C-cleaved side products were present at more than negligible level in all the three reactions. It has been reported that large extein protein could promote cleavage side reactions 38 , and the use of large extein (Fab and Fc) in combination with large MBP on the other side of intein might be disadvantageous.…”
Section: Resultsmentioning
confidence: 92%
“…Interestingly, the higher concentration of 2 M NaCl showed worse cleavage than the 0.5 M NaCl for exenatide-IIST. Despite the long incubation with the optimized salt condition, the cleavage of the tag was incomplete, suggesting that the junction amino-acid type of “Ser” might influence cleavage efficiency as reported for the IMPACT™ system ( Figure 5 e) [ 5 , 28 , 29 ].…”
Section: Resultsmentioning
confidence: 97%
“…The Hut MCM2 intein has the wild-type Arg at the so-called -1 position [ 12 , 16 ]. The protein-splicing activity of the Hut MCM2 intein was the best when the -1 position was Arg in the model system [ 29 ]. We estimated the cleavage efficiency of the GLP-1 analog to be >80% after 18 h ( Figure 6 b).…”
Section: Resultsmentioning
confidence: 99%